Sodium-induced phase shift in ?-NaMnO2 and electrochemical properties of the full cells using hard carbon anodes derived from regional olive leaves - Dogan, Ebru; Ozcan, Sibel; Canbay, Canan Aksu; Karta, Mesut; Depci, Tolga; Altin, Serdar (Springer Japan Kk, 2025)
In this study, we investigated the effect of excess sodium (Na) in a NaMnO2 structure using one-step heat treatment at 900 degrees C followed by quenching in liquid nitrogen (N-2). According to the X-ray diffraction (XRD) analysis, there was a competition between the monoclinic and orthorhombic phases, and we found that there were two monoclinic phases with similar structural properties. Therefore, we focused on revealing the formation of two isostructures of the monoclinic phase triggered by Na ions. We found that the lattice parameters and beta angle changed from 113 degrees to 105 degrees in the samples with increasing Na content. Structural analysis of the powders using the XRD data was conducted using Rietveld refinement, and the phase ratios for all samples were calculated. The sample with x = 1.3 showed a 95% alpha-phase. To understand the formation of the two isostructures, we performed Density functional theory (DFT) calculations to examine their band structure, stability, and formation energy. A structural analysis of the excess Na-doped samples was performed using common techniques, and it was found that excess Na caused the formation of a coating on the grains in the form of sodium oxide. To validate this prediction, we conducted inductively coupled plasma mass spectrometry (ICP-MS), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy coupled with energy dispersive X-ray (SEM-EDX) analyses using the basic properties of these techniques and their interactions with materials. In the second part of the study, we produced HC from locally sourced olive leaves and investigated their structural properties. The electrochemical properties of the electrode materials were examined using a half-cell configuration as electrodes with Na metal and a full-cell configuration using x = 1.3 cathode and HC anode. A direct-contact pre-sodiation strategy was used as the anode in the full-cell measurements. It was found that the full cells had initial capacity values of 150 mAh/g for the voltage range 1.5-4.3 V and 120 mAh/g for the voltage range 1.5-3.5 V.
Keywords: NaMnO2; Excess Na; Na-ion full cell; HC